An evaluation of pattern of adverse drug reactions reporting by undergraduate medical students in a tertiary care hospital - Bali, Zorawar Singh; Bhat, Mohammad Younis; Farhat, Samina; Nabi, Urfan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions (ADRs) are an important cause of mortality and morbidity worldwide and reporting ADRs voluntarily is fundamental to medical drug safety surveillance but gross underreporting of ADRs is a cause for a concern. Being key health care professional, physicians, pharmacists and nurses have immense responsibility in reporting of ADRs. Therefore, the sensitization and involvement of undergraduate medical students can reduce underreporting. This study is aimed at evaluating knowledge, attitude and reporting of quality of ADRs by undergraduate medical students. Methods: The study was conducted after sensitizing the second professional year undergraduate students about Pharmacovigilance as part of their internal assessment and asked them to submit reports of ADR observed during their clinical posting. Results: A total of 82 ADR’s were reported after sensitization with majority of them i.e. 30 related to skin and appendages disorder followed by gastrointestinal tract with antibiotics i.e. 28 and analgesics being most common probable/possible culprits. Conclusions: The response percentage of reporting ADRs was 54.66%. Medical students being future healthcare professionals should be exposed to ADR reporting during their clinical teaching posting as a part of sensitization and make them actively involved in reporting to improve detection rate and make Pharmacovigilance a success.